2015
DOI: 10.1039/c4tb01680g
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the cross-linking and degradation mechanism of Diels–Alder hydrogels

Abstract: Eight-armed poly(ethylene glycol) was functionalized with furyl and maleimide groups. The two macromonomers were cross-linked by Diels-Alder (DA) reactions and the degradation behavior of the formed hydrogels was investigated. UV spectroscopy showed that maleimide groups were subject to ring-opening hydrolysis above pH 5.5, with the reaction rate depending on the pH and temperature. As a result of this, the gelation kinetics and stiffness of DA hydrogels were dependent on the temperature and the pH of the cros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 37 publications
(79 reference statements)
2
55
0
Order By: Relevance
“…18, 19 The mesh size of 8armPEG10k-hydrogels was determined using swelling studies, rheology and low field NMR spectroscopy. The calculated values of ξ allowed us to estimate the release 15 rate of fluorescein isothiocyanate-labeled dextran (FD); four different molecular masses (4 kDa, 20 kDa, 150 kDa and 500 kDa) were studied.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…18, 19 The mesh size of 8armPEG10k-hydrogels was determined using swelling studies, rheology and low field NMR spectroscopy. The calculated values of ξ allowed us to estimate the release 15 rate of fluorescein isothiocyanate-labeled dextran (FD); four different molecular masses (4 kDa, 20 kDa, 150 kDa and 500 kDa) were studied.…”
Section: Introductionmentioning
confidence: 99%
“…Since the D g values can be calculated from eqn. (19) and (20) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 21 where M t and M ∞ represent the absolute cumulative amounts of FD released at time t and infinity, respectively; q n are the roots of the Bessel function of the first kind of zero order, and r and h denote the radius and height of the gel cylinder. The increase in r and h due to swelling is taken into account, and the predicted release profiles are shown in Figure 5B.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Finally, the degradation rate of DA hydrogels is governed by the hydrolytic stability of the involved maleimide groups. 25 It has been shown that degradation occurs by retro-Diels-Alder (rDA) reaction and subsequent ring-opening hydrolysis of the newly generated maleimide groups. The rate of the rDA reaction is low at 37 1C; however, ring-opening hydrolysis of maleimide to unreactive maleamic acid shifts the DA/rDA equilibrium and significantly accelerates the degradation rate.…”
Section: Swelling Degradation and Antibody Releasementioning
confidence: 99%